Comparative effects of calcium channel antagonism and beta-1 selective blockade on exercise performance in physically active hypertensive patients - Selvey, Christine Enid (MRC/UCT RU for Exercise and Sport Medicine, 2017)
The current recommendations by the American Heart Association for health promotion are that all persons should partake in regular physical activity in order to reduce the risk of cardiovascular disease. Regular physical exercise reduces blood pressure and is an important component of the management of hypertension. It is therefore important that patients with hypertension participate in habitual physical exercise. Many hypertensive patients who exercise will require anti-hypertensive medication. However, some antihypertensive agents cause fatigue during exercise. In order for patients to gain the full benefits of an active lifestyle, it is important that the prescribed antihypertensive agent does not prevent them performing and enjoying sustained exercise. It has been well documented that β-blockers cause premature fatigue during physical exercise. The effects on exercise performance of other first line antihypertensive medications, such as calcium channel antagonists have not been extensively investigated. In particular, the effects of these agents on prolonged submaximal exercise endurance have not been well studied. The object of this thesis was to compare the effects of isradipine, a dihydropyridine calcium channel antagonist, to those of atenolol, a β₁-selective antagonist, on maximal and submaximal exercise performance and on short duration high-intensity exercise in physically active hypertensive patients. The study design was a crossover trial where drug treatments were double blinded and randomised. Physically active volunteers with mild to moderate hypertension were recruited. 11 subjects performed i) progressive exercise to exhaustion for determination of maximal oxygen consumption (VO₂max), maximal work load and cardiorespiratory responses to maximal exercise, ii) prolonged submaximal exercise for determination of exercise endurance, cardiorespiratory responses and ratings of perceived exertion (APE), and iii) short duration, high intensity exercise consisting of a 30 second maximal exercise test (Wingate test) to determine skeletal muscle power output, following 4 weeks ingestion of isradipine (2.5mg bd), atenolol (50mg bd) or placebo. Diastolic blood pressure at rest was reduced by both atenolol and isradipine, but was lowered to a greater extent by atenolol (83.3 vs 89.0 vs 96.1 mmHg, atenolol vs isradipine vs placebo, p<.0005). Systolic blood pressure at rest tended to be similarly reduced by both agents, but was significantly reduced during maximal and submaximal exercise by atenolol only (p<.001, atenolol vs isradipine, placebo). Heart rate at rest and during maximal and submaximal exercise was decreased by atenolol only (p<.0005, atenolol vs isradipine, placebo). Maximal exercise performance was reduced after atenolol ingestion compared to placebo but not after isradipine ingestion. Peak workload achieved during the maximal exercise test was decreased after atenolol but unchanged after isradipine ingestion (214 vs 243 W, atenolol vs placebo, p<.01). Similarly, VO₂max was reduced after atenolol compared to placebo but was unchanged after isradipine ingestion (33.6 vs 36.4, 33.6 vs 36.1 mlO₂/kg/min, atenolol vs placebo, atenolol vs isradipine, p<.05). Both atenolol and isradipine ingestion reduced submaximal endurance time compared to placebo (27.8 vs 46.4, 34.4 vs 46.4 min, atenolol vs placebo, isradipine vs placebo, p<.005), and increased rating of perceived exertion (APE) after 30 min of submaximal exercise (p<.05). Submaximal oxygen consumption (VO₂), ventilation, respiratory exchange ratio (REA) and blood lactate, glucose and free fatty acid concentrations were not altered after the ingestion of either agent. Neither agent influenced peak skeletal muscle power, total work done, or rate of fatigue during the Wingate test compared to placebo. The results of these studies indicate that impaired performance and increased RPE during submaximal exercise after ingestion of either atenolol or isradipine is not due to alterations of ventilation, VO₂, RER, or blood lactate, glucose and free fatty acid concentrations during prolonged submaximal exercise. Similarly, reduced submaximal exercise performance after atenolol or isradipine ingestion is not due to factors which would also limit the ability of skeletal muscle to perform short duration, high intensity exercise before a bout of prolonged exercise. This study demonstrates that prolonged submaximal exercise testing can reveal an impairment in exercise performance after ingestion of antihypertensive medication which is not evident during maximal exercise testing. This finding is important as prolonged submaximal exercise is the form of exercise which most hypertensive patients actually perform. Further research is required on the effects of anti-hypertensive medications on submaximal exercise performance before firm recommendations can be made regarding medications most suitable for the physically active hypertensive patient. The results of these and other studies indicate that it is not yet possible to make claims that the calcium channel antagonist agents are without effect on physical exercise performance in physically active hypertensive patients.